Occurrence and fate of endotoxin activity at drinking water purification plants and healthcare facilities in Japan. (15th November 2018) - Simazaki, Dai; Hirose, Masaaki; Hashimoto, Hisashi; Yamanaka, Shunji; Takamura, Mitsuteru; Watanabe, Junya; Akiba, Michihiro
Abstract: Occurrence of residual endotoxin activity (ET) in dialysis water and also tap water as its source is a matter of great concern to medical professionals conducting dialysis therapy at healthcare facilities (HCFs). The present study was performed to determine the occurrence and fate of the ET at selected Japanese drinking water purification plants and HCFs between 2014 and 2016. Chemical coagulation and sedimentation, rapid sand filtration, and membrane filtration were highly effective to decrease both ET dissolved in water (free-ET) and ET bound to cells/particles (bound-ET). Moderate decreases in bound-ET and limited decreases in free-ET were observed by chlorination and ozonation. Bacterial activated carbon filtration was a major cause of significant increases in endotoxin activity during the course of drinking water purification process. Levels of residual ET in water supplied to HCFs were strongly affected by their source waters and the configurations of water purification processes served. Microbial regrowth on the premises, from water tanks to faucets at HCFs could also contribute to ET increases in tap water. Graphical abstract: Image 1 Highlights: Endotoxin activity (ET) in water for dialysis therapy is of critical concern. The occurrence of ET was determined in the course of water purification processes. Chemical coagulation followed by rapid sand filtration significantly reduced ET. Biological activated carbon increased free- and bound- ET significantly. Microbial regrowth in healthcare plumbing systems can result in increased ET.